2023
DOI: 10.3390/electronics12040827
|View full text |Cite
|
Sign up to set email alerts
|

Design of Efficient Methods for the Detection of Tomato Leaf Disease Utilizing Proposed Ensemble CNN Model

Abstract: Early diagnosis of plant diseases is of vital importance since they cause social, ecological, and economic losses. Therefore, it is highly complex and causes excessive workload and time loss. Within the scope of this article, nine tomato plant leaf diseases as well as healthy ones were classified using deep learning with new ensemble architectures. A total of 18.160 images were used for this process. In this study, in addition to the proposed two new convolutional neural networks (CNN) models, four other well-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…The curves (Figs. 13 and 14) demonstrate the diagnostic ability of various classifiers on tomato health status at the discriminating threshold [31]. A perfect classifier should have a true positive rate of 1 and a false positive rate of 0.…”
Section: Performance Comparison Of Classification Algorithms On Embed...mentioning
confidence: 97%
“…The curves (Figs. 13 and 14) demonstrate the diagnostic ability of various classifiers on tomato health status at the discriminating threshold [31]. A perfect classifier should have a true positive rate of 1 and a false positive rate of 0.…”
Section: Performance Comparison Of Classification Algorithms On Embed...mentioning
confidence: 97%
“…The majority of previous approaches to disease detection relied on artificial recognition techniques, such as (1) making predictions about the sorts of illnesses based on farmers' years of crop cultivation experience or (2) consulting agricultural information books. To (2) research available options, one may collect images of illness specimens and do an online search. Third, get in touch with experts to help you explore the signs of sickness.…”
Section: Figure 1 Tomato Leaf Samples With Various Diseasementioning
confidence: 99%
“…Karthik et al (2020), for example, created an attention-embedded residual CNN for disease identification in tomato leaves and attained an overall accuracy of 98% in a 5-fold cross-validation [1]. The remarkable accuracy of 99.60% has been achieved by Ulutaş and Aslantaş's (2023) ensemble CNN model for the identification of tomato leaf diseases [2]. Gehlot and Saini (2020) examined many CNN architectures for tomato leaf disease categorization and found that DenseNet-121, VGG16, and ResNet-101 performed well with comparable accuracy, precision, recall, and F1-score [3].…”
Section: Related Workmentioning
confidence: 99%
“…The ResNet152V2 model was selected due to its prevalence in image classification literature in a variety of different fields from disease ratings in agriculture (Kanchanadevi & Sandhia, 2023;Nigam et al, 2023) to medical research (Sulaiman et al, 2023). The final model was the pre-trained EfficientNetV2L model (Tan & Le, 2021), which was selected due to its recent use in plant disease detection (Shovon et al, 2023;Ulutaş & Aslantaş, 2023). Mean squared error (MSE) was used as the loss function for each model, which evaluates differences between values predicted by the model and their true value.…”
Section: Deep Learningmentioning
confidence: 99%